The Egypt game - Snyder, Zilpha Keatley; Raible, Alton, 1918- (New York : Dell, 1986)
A group of children, entranced with the study of Egypt, are visited by a secret oracle, become involved in a murder, and befriend the Professor
5-7.
1010
Accelerated Reader AR
Keywords: Egypt -- Antiquities -- Fiction